Determination of alkaloids and phenols in the chewable husk products of Areca catechu L. Using HPLC-UV and UHPLC-MS/MS. Issue 10 (15th June 2018) - Yuan, Hanwen; Cao, Mengru; Yi, Pan; Xie, Qingling; Jian, Yuqing; Li, Bin; Qin, Yan; Peng, Caiyun; Wu, Hangyu; Tan, Dianbo; Qin, Yuhui; Wang, Wei
Abstract: The chewable husk products of Areca catechu L., named "Binglang" including Qingguo and Yanguo are widely used as a stimulant by people in southern China. However, no quality control analytical method has yet been developed for chewable Binglang. A high performance liquid chromatography coupled with UV detector (HPLC-UV) method for quantitative analysis of four characteristic areca alkaloids is being reported here. In addition, an ultra high-pressure liquid chromatography tandem mass spectrometry (UHPLC-MS/MS) method for determination of usually overlooked constituents of Binglang products, including eight phenols, and one minor alkaloid has also been developed for the first time. Moreover, fingerprint similarity evaluation, and pattern recognition including principle component analysis (PCA) and random forest (RF) were applied to analyze the obtained spectrometric data. The results firstly revealed substantial variations in the levels of areca alkaloids among Qingguo, Yanguo, raw husk, and the seed products. Two phenols, i.e. (+)-catechin and p -hydroxybenzoic acid, among the analytes were found to be considerably high in the husk products. This study presents the first important step toward providing a systematic method for comprehensive quality control of Binglang products. Graphical Abstract: